Altering the viscoelastic properties of mucus-grown Pseudomonas aeruginosa biofilms affects antibiotic susceptibility - Kaitlyn R. Rouillard; Matthew R. Markovetz; William J. Kissner; William L. Boone; Lucas M. Plott; David B. Hill (Biofilm, 2023)
The viscoelastic properties of biofilms are correlated with their susceptibility to mechanical and chemical stress, and the airway environment in muco-obstructive pulmonary diseases (MOPD) facilitates robust biofilm formation. Hyperconcentrated, viscoelastic mucus promotes chronic inflammation and infection, resulting in increased mucin and DNA concentrations. The viscoelastic properties of biofilms are regulated by biopolymers, including polysaccharides and DNA, and influence responses to antibiotics and phagocytosis. We hypothesize that targeted modulation of biofilm rheology will compromise structural integrity and increase antibiotic susceptibility and mucociliary transport. We evaluate biofilm rheology on the macro, micro, and nano scale as a function of treatment with a reducing agent, a biopolymer, and/or tobramycin to define the relationship between the viscoelastic properties of biofilms and susceptibility. Disruption of the biofilm architecture is associated with altered macroscopic and microscopic moduli, rapid vector permeability, increased antibiotic susceptibility, and improved mucociliary transport, suggesting that biofilm modulating therapeutics will improve the treatment of chronic respiratory infections in MOPD.